PENAMBAHAN SARI BUAH BELIMBING WULUH (Averrhoa bilimbi) PADA PAKAN UNTUK MENGOBATI IKAN LELE SANGKURIANG (Clarias sp.) YANG DIINFEKSI Aeromonas hydrophila - Herdia Agustina; Ade Dwi Sasanti; Marini Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACT Motile Aerhomonas Septicemia (MAS) is one of bacteria diseases which is often attack freshwater fish. Motile Aerhomonas Septicemia (MAS) or hemmorage septicemia caused by bacteria A. hydrophila. The aim of this reserch examine Averrhoa bilimbi juice mixed on feed in order to effect sangkuriang catfish by A. hydrophila. The research was conducted at September until October 2016 in Laboratorium Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya and Laboraturium UPT Klinik Universitas Sriwijaya. Method of the research uses Completely Ranomized Design with six treatments and three replications. This research was conducted for 25 days of rearing. The catfish given feed mixed A. b          ilimbi juice about 150 mL.kg-1 (P1), 200 mL.kg-1 (P2), 250 mL.kg-1 (P3) dan 300 mL.kg-1 (P4) with frequency was three times a day. The parameters of this reserch is wound diameter, the percentage of cured fish, hematocrit, growth, food convertion ratio, survival rate, and chemical properties (temperature, pH, DO and ammonia). The results showed that the addition of A. bilimbi juice at P1 be obtained the percentage of cured fish was 64.47% and survival rate was 71.11%. P2 be obtained the percentage of cured fish was 68.89% and survival rate was 73.33%. P3 be obtained the percentage of cured fish was 72.53% and survival rate was 80.00%. P4 be obtained the percentage of cured fish was 95.40% and survival rate was 95.56%. P4 with dose 300 mL.kg-1 feed is the best treatment bacterial A. hydrophila infection of hematocrit was 32%, the percentage of cured fish was 95.40%, and survival rate was 95.56%. Water quality parameters during maintenance is still in a state of optimum range. Keywords: Aeromonas hydrophila, Sangkuriang catfish, Averrhoa bilimbi juice.